Predicting future axial length in patients with paediatric cataract and primary intraocular lens implantation - Lottelli, Antonio Carlos [UNESP] (SAGE Publications, 2020)
Objective: Creating a model to predict Axial Length (AL) growth in paediatric cataract and evaluating influence factors. Material and methods: Eyes with AL measured at surgery and at least one measurement after a 6-month period, from children with unilateral or bilateral cataract and primary IOL implantation, were evaluated. A “rate of axial length growth” (RALG) was calculated for every single eye using these AL measurements and log10 age. One average RALG was calculated for All Eyes and for the groups of Bilateral and Unilateral, Gender, Age at the Surgery, different Visual Acuity, Bilateral Excluded and Not-excluded eye, and Affected and Not-affected eye in unilateral, for comparisons. Results: Average age at surgery from 76 children was 2.83 ± 2.74 (0.11–12.21) years with follow up of 2.84 ± 1.84 (0.52–8.17) years, 29 (37.66%) had unilateral cataract. A total of 357 AL measurements were used, average of 4.70 ± 2.13 (2–10) measurements per eye. The average RALG for all eyes was 4.51 ± 3.06. There were no RALG significant differences comparing Unilateral and Bilateral eyes (p = 0.51), Male and Female (p = 0.26), Age at Surgery <0.5 and >0.5 years old (p = 0.21), both eyes in Bilateral cases (p = 0.70) and Unilateral Affected and Not-affected eyes (p = 0.18). The equation Al = initial AL + slope × Log10 ((age + 0.6)⁄(initial age = 0.6)) estimates ALs in different ages. Conclusions: A model to predict AL growth in paediatric cataract was developed. Different studied factors did not significantly influence AL growth.
Keywords: anterior segment disease (includes cataract); biometry/axial length; childhood cataract surgery; IOL calculation for primary/secondary IOL; lens/cataract; Pediatric ophthalmology